Rancang Bangun Pengaruh Variasi Penambahan Aluminium Pada Paduan Tembaga Terhadap Konduktivitas Termal Bahan - Rian Eka Putra, I Putu; Astika, I Made; Sukadana, I Gusti Ketut (Teknik Desain Mekanika, 2021)
Abstract This study aims to analyze the effect of variations in the addition of aluminum to copper alloys on thermal conductivity. The analysis in this study used independent variables, namely variations in the addition of aluminum by 10%, 20% and 30% in copper alloys. Meanwhile, the dependent variable is thermal conductivity. The thermal conductivity test uses the TQ Heat Transfer Experiment Base Unit tester. The dimensions of the test specimens were 30 mm in diameter and 20 mm thick. The result of this research is that the thermal conductivity tends to decrease with the addition of aluminum to the copper alloy. Keywords: Copper alloy, aluminum, thermal conductivity